On the Analysis of Semantic Groups (Nouns Denoting Joint Collectivity in Present-Day English) - Астраускайте, Даля (Kalbotyra, 1985)
The article presents a review of the existing opinions on the theory of semantic groups of words. Semantic groups serve as a means of structural organization of the lexical system of language and are defined as groups of words within one and the same pari of speech related through their partial semantic similarity, i. e. all constituents of the given group have at least one common semantic component and one or more different semantic components. The constituents of the group of nouns which denote joint collectivity are related by means or the integral semantic component ‘a number of’ (e. g. company, clan, pack). Words belonging to this semantic group serve as lexical means of expressing the category of quantity – one of the most important categories of existence. According to the way in which the meaning of a collectively joined number of objects is expressed, nouns of this group fall into three subgroups: (1) nouns denoting the total number of certain objects (e. g. peerage, suite); (2) nouns denoting an indefinitely large number of objects (e. g. clan, galaxy, swarm); (3) nouns denoting an indefinitely small number of objects (e. g. cluster, packet).